2022
DOI: 10.1111/imj.15817
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term outcomes of patients with chronic liver disease hospitalised with COVID‐19

Abstract: Background and aims Patients with chronic liver disease (CLD) might have aggravated course upon acquisition of coronavirus disease 2019 (COVID‐19). We aimed to analyse the outcomes of patients with CLD who were hospitalized due to COVID‐19. Methods Medical records of 4014 patients hospitalized due to COVID‐19 in a regional referral hospital over a 12‐month period were analysed. Patients with CLD were identified based on discharge diagnoses according to ICD‐10 classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
(118 reference statements)
1
6
0
Order By: Relevance
“…Similarly, hospitalisations for CC+ were higher in patients above 70 years of age, as well as patients with comorbidities. This is consistent with current literature reports [13,20,27].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Similarly, hospitalisations for CC+ were higher in patients above 70 years of age, as well as patients with comorbidities. This is consistent with current literature reports [13,20,27].…”
Section: Discussionsupporting
confidence: 94%
“…There have been few studies characterising the outcomes of patients with cirrhosis and COVID-19 based on the etiology of cirrhosis. In a single-center study of patients with chronic liver disease of mostly alcoholic etiology, hospitalised for COVID-19, presence of cirrhosis was associated with fourfold increase in 30 day mortality compared to patients without cirrhosis [13]. Yoo et al showed that patients with pre-existing NAFLD have a higher likelihood of testing positive for COVID-19, and are more predisposed to severe illness [14].Additionally, Kim et al showed that the etiology of all-cause mortality from alcoholic liver disease and non-alcoholic fatty liver disease increased significantly during the COVID-19 pandemic, with increase in cirrhosis-related mortality mainly attributable to alcoholic liver disease [15].…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, a study by Sohail et al identified chronic kidney disease, cardiovascular diseases, and intensive care admission as predictors for mortality in cirrhotic patients hospitalized with COVID-19 23 . However, other studies have found that chronic kidney disease and cardiovascular diseases were not predictors for mortality in cirrhotic patients hospitalized with COVID-19 infection 24,25 . In this study, both WBC and serum albumin were found to be predictors of death in cirrhotic patients with COVID-19.…”
Section: Discussionmentioning
confidence: 82%
“…One of the remarkable findings in our patient group is that almost a quarter of them were infected with COVID-19, despite the patient cohort were being well-informed and had strictly adhered to precautions in the pre-vaccine period. Cirrhosis has been shown in a recent study as a risk factor for short-term mortality ( 17 ). COVID-19 infection was fatal in 16% of our patients.…”
Section: Discussionmentioning
confidence: 98%